Phase angle adjustment for phase advance control of brushless DC motor - Syafiq Bin Mohd, M. (IEEE Computer Society, 2014)
Brushless direct current (BLDC) motor is widely used in small and medium side electric vehicles as it exhibit highest specific power and thermal efficiency compared with induction motor. The permanent magnets in the rotor create a constant magnetic flux, which limit the motor top speed. As the back electromotive force (EMF) voltage increases proportionally with motor rotational speed and it approaches the amplitude of the input voltage, the phase current amplitude will reach zero. By advancing the phase current, it is possible to extend the maximum speed of the BLDC motor beyond the rated top speed. This will allow smaller BLDC motor to be used in small electric vehicles and in larger applications will allow the use of BLDC motor without the use of multispeed transmission unit for high speed operation. Adjusting the phase angle will affect the speed of the motor as the each coil is energized earlier than the corresponding rise in back emf of the coil. Preliminary test results indicated that the motor top speed can be increased at least by 40 percent over the baseline speed at no load condition. Â© 2014 IEEE.